Sensitive Controversy in Teaching to Be Critical - Forrest, Michelle (Paideusis, 2009)
The sensitive nature of certain controversies is particularly problematic for teaching across difference. Questions as to what makes a controversy sensitive and how care and empathy are implicated in discussing it are considered through examples connected to the author’s own practice and in light of the traditional rationalist concept of critical spirit and feminist strong reflexivity. The suggestion is made that discussing sensitive controversy requires a ‘doubled view’ and that this is needed at all levels of inquiry.